2001
DOI: 10.1038/90042
|View full text |Cite
|
Sign up to set email alerts
|

PAX6 haploinsufficiency causes cerebral malformation and olfactory dysfunction in humans

Abstract: PAX6 is widely expressed in the central nervous system. Heterozygous PAX6 mutations in human aniridia cause defects that would seem to be confined to the eye. Magnetic resonance imaging (MRI) and smell testing reveal the absence or hypoplasia of the anterior commissure and reduced olfaction in a large proportion of aniridia cases, which shows that PAX6 haploinsuffiency causes more widespread human neuro developmental anomalies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
144
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 209 publications
(152 citation statements)
references
References 13 publications
6
144
1
1
Order By: Relevance
“…It will be interesting to know the effect of homozygous mutations in e5a if we ever find one. Humans and mice with mutations in Pax6 show abnormality in brain and pancreas (12,31). However, Azuma et al (30) reported that, except for one, patients with mutations in e5a had normal growth and intelligence.…”
Section: Resultsmentioning
confidence: 99%
“…It will be interesting to know the effect of homozygous mutations in e5a if we ever find one. Humans and mice with mutations in Pax6 show abnormality in brain and pancreas (12,31). However, Azuma et al (30) reported that, except for one, patients with mutations in e5a had normal growth and intelligence.…”
Section: Resultsmentioning
confidence: 99%
“…Using this paradigm, we have demonstrated roles for the genes PAX6, PITX2, SOX2, OTX2 and RIMS1 in human brain development and cognitive function. [1][2][3][4] Mutations in PROM1 have been shown to result in retinitis pigmentosa, 5,6 macular degeneration 7,8 and cone-rod dystrophy. 9 PROM1 encodes prominin-1, a 5-transmembrane glycoprotein also known as CD133 and AC133.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that a precise range of the Pax6 protein level is important for the proper development of the eyes, brain, and pancreas because an increase of Pax6 expression in transgenic mice leads to abnormalities in these organs (19,20,34). Moreover, heterozygous Pax6 individuals display anomalies in eye morphology and brain patterning (10). However, no obvious morphological abnormality has been reported yet at the level of the pancreas in Pax6 heterozygous mice, and we did not detect any obvious anomalies in pax6b sa0086 heterozygous larvae (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…These truncated Pax6 mutant mice exhibit a phenotype essentially identical to that of Pax6/ LacZ knock-out mice (9) and are thus considered as null mutants. Although heterozygous Pax6 mutants display eye malformations (reduced lens size, iris and corneal anomalies) and some forebrain patterning defects (10,11), no obvious morphological abnormalities have been detected in the pancreas. Yet mice and human patients heterozygous for a Pax6 mutation often display impaired glucose tolerance at the adult stage (12,13).…”
mentioning
confidence: 99%